Innovation and Investment Funding in the Post-Crisis Period: Have Financing Patterns and Financial Constraints of German Firms Changed? - Dorothea Schäfer; Andreas Stephan (Vierteljahrshefte zur Wirtschaftsforschung, 2017)
This study examines the actual funding behavior of German innovative firms in the pre- and postcrisis period. Specifically, we investigate if and how the funding patterns and financial constraints of German small and medium enterprises (SME) changed during and since the financial crisis. The purpose of our analysis is to assess whether the aims of the European CMU action plan, funding innovation and investment activities, complements the behavior of German SMEs. We find fairly stable funding patterns over the years and there is no indication that financial constraints have become tighter in the post-crisis period. Consequently, realizing the CMU's central goal of broadening the funding mix could leave the funding behavior of German SMEs largely unaffected. – – Diese Studie untersucht das aktuelle Finanzierungsverhalten deutscher innovativer Unternehmen vor und nach der Finanzkrise. Speziell untersuchen wir, ob sich die Finanzierungsstruktur und finanzielle Restriktionen der deutschen kleinen und mittleren Unternehmen (KMU) seit der Finanzkrise verändert haben. Der Zweck unserer Analyse ist es, zu beurteilen, ob die Ziele des europäischen CMU-Aktionsplans, insbesondere das Ziel der Förderung von Innovations- und Investitionstätigkeit, die Finanzierungssituation von deutschen KMU tatsächlich verbessern kann. Wir finden über den Untersuchungszeitraum hinweg stabile Finanzierungsstrukturen, und wir finden keine Evidenz, dass finanzielle Restriktionen nach der Krise zugenommen hätten. Vor diesem Hintergrund wird der CMU-Aktionsplan mit der Zielsetzung, den Finanzierungsmix von KMU zu erweitern, das aktuelle Finanzierungsverhalten deutscher KMU kaum beeinflussen.
Keywords: G32; G38; G01; 330; Capital Markets Union; SMEs; funding behaviour; financial structure